2021
DOI: 10.3168/jds.2020-18943
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress affects some physiological and productive variables and alters metabolism in dairy ewes

Abstract: Heat stress (HS) has a significant economic impact on the global dairy industry. However, the mechanisms by which HS negatively affects metabolism and milk synthesis in dairy ewes are not well defined. This study evaluated the production and metabolic variables in dairy ewes under controlled HS conditions. Eight Lacaune ewes (75.5 ± 3.2 kg of body weight; 165 ± 4 d of lactation; 2.31 ± 0.04 kg of milk per day) were submitted to thermoneutral (TN) or HS conditions in a crossover design (2 periods, 21 d each, 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The lowest concentration of CRT among periods in period 1 may reflect minimal protein catabolism with thermoneutral conditions. Similarly, thermal challenges to dairy ewes [ 45 ] and goats [ 46 ] increased blood CRT concentration, suggesting that heat stress causes muscle degradation. That the level of TP was lower in period 4 vs. 1 despite this difference in CRT could involve relatively high water intake and body water content in period 4.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest concentration of CRT among periods in period 1 may reflect minimal protein catabolism with thermoneutral conditions. Similarly, thermal challenges to dairy ewes [ 45 ] and goats [ 46 ] increased blood CRT concentration, suggesting that heat stress causes muscle degradation. That the level of TP was lower in period 4 vs. 1 despite this difference in CRT could involve relatively high water intake and body water content in period 4.…”
Section: Discussionmentioning
confidence: 99%
“…Barki sheep practiced more deep breathing to cope with the needed energy for physical exercise under heat stress, than Barki Goats. Mehaba, et al (2021) reported significant increase in RR and GV in heat stressed dairy ewes, compared to that under thermo-neutral conditions. GV (l/min) 2.1b ± 0.05 (1.0-3.4)…”
Section: Resultsmentioning
confidence: 80%
“…Climatic variables can affect metabolism, and consequently, surface temperature and rectal temperature in buffaloes ( 47 ), as well as in Nelore ( 48 ) and dairy cows ( 49 , 50 ).…”
Section: Resultsmentioning
confidence: 99%